Thread and communication a visual manifestation of re-connecting with a dear departed - Astejada, Samuel Bien Sandro T.
Reconnecting with a dear departed is what every person left behind wishes for. Such is the wish of this proponent. The death of his parents is so heartbreaking that the loss made him withdrew for a while from the world he used to live in with his parents and retreated to a place of isolation. While in that place, he developed a way to cope with his loss: he started to write his thoughts on pages of notebooks and journals, words that he would have spoken to his parents if they were still alive. In his own way, he kept a "connection" with his departed parents through his writings on pages of paper.